1968
DOI: 10.1346/ccmn.1968.0160307
|View full text |Cite
|
Sign up to set email alerts
|

Boron Fixation by Illites

Abstract: Abstract-The mechanism of boron uptake by clays, especially illitic clays, and the factors which control such uptake have long been debated issues. In an attempt to answer some of the questions of the controversy, three illites were treated in solutions containing boron. In the study, boron concentration, salinity, temperature, and time were varied independently over rather wide ranges.For the illites studied, irreversible uptake of boron was increased by increasing boron concentration, salt concentration, tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
4

Year Published

1974
1974
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 17 publications
1
34
0
4
Order By: Relevance
“…This suggests, in accordance with Couch and Grim (1968) and , that boron is adsorbed on the clay edges rather than on the planar surfaces. The difference in boron adsorption between the Na and Ca forms of the two clays is discussed below.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This suggests, in accordance with Couch and Grim (1968) and , that boron is adsorbed on the clay edges rather than on the planar surfaces. The difference in boron adsorption between the Na and Ca forms of the two clays is discussed below.…”
Section: Resultssupporting
confidence: 81%
“…Such specific ad-1 Journal article 856, Agricultural Experiment Station, New Mexico State University, Las Cruces, New Mexico 88003. sorption can occur independent of the sign of the net surface charge (Hingston et al, 1972) and involves the boron species B(OH)3 and B(OH)4-. Several investigators (Couch and Grim, 1968;Bingham and Page, 1971; suggested that most of the boron adsorption sites were located on broken edges of the clay particles. Thus, the magnitude of boron adsorption on montmorillonite and illite should be similar regardless of the exchangeable ions, because the surface area of the broken edges of both clays is essentially the same.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators (Couch and Grim, 1968;Bingham and Page, 1971) suggested that most of the clay's i Contribution No. 231-E, 1980 series.…”
Section: Introductionmentioning
confidence: 99%
“…Boron is retained in soils by adsorption onto mineral and humic particles and by forming insoluble precipitates (Couch and Grim 1968;Goldberg and Glaubig 1985;Evans 1987). The mobility, transport and partitioning of B in soils are dependent on various soil chemical properties that include soil pH, the type and contents of clay minerals, and the contents of Al and Fe oxides and (oxy)hydroxides, carbonates and organic matter .…”
mentioning
confidence: 99%